2019
DOI: 10.3390/foods8090372
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistant Pseudomonas Spp. Spoilers in Fresh Dairy Products: An Underestimated Risk and the Control Strategies

Abstract: Microbial multidrug resistance (MDR) is a growing threat to public health mostly because it makes the fight against microorganisms that cause lethal infections ever less effective. Thus, the surveillance on MDR microorganisms has recently been strengthened, taking into account the control of antibiotic abuse as well as the mechanisms underlying the transfer of antibiotic genes (ARGs) among microbiota naturally occurring in the environment. Indeed, ARGs are not only confined to pathogenic bacteria, whose diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 192 publications
(209 reference statements)
1
51
1
1
Order By: Relevance
“…Only few species are classified opportunistic human pathogens and phytopathogens ( Pseudomonas aeruginosa, Pseudomonas syringae , and Pseudomonas cichorii ; de Bentzmann and Plésiat, 2011 ; Ichinose et al, 2013 ). However, an increasing number of Pseudomonas strains, without the issue of pathogenicity, have displayed multiple drug resistances, raised from horizontal transfer of genetic elements or inheritable mutations, which pose a severe threat to human health ( Guzel et al, 2018 ; Quintieri et al, 2019a ). Moreover, the isolation of non-pathogenic pseudomonads strains from clinical human cases has rapidly increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few species are classified opportunistic human pathogens and phytopathogens ( Pseudomonas aeruginosa, Pseudomonas syringae , and Pseudomonas cichorii ; de Bentzmann and Plésiat, 2011 ; Ichinose et al, 2013 ). However, an increasing number of Pseudomonas strains, without the issue of pathogenicity, have displayed multiple drug resistances, raised from horizontal transfer of genetic elements or inheritable mutations, which pose a severe threat to human health ( Guzel et al, 2018 ; Quintieri et al, 2019a ). Moreover, the isolation of non-pathogenic pseudomonads strains from clinical human cases has rapidly increased.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, indeed, pigments modulate the transition to planktonic to biofilm state ( Mavrodi et al, 2013 ), show antimicrobial effects against other microorganisms ( Gram, 1993 ), protect cells from oxidative stress and can act as signaling molecules and virulence factors ( Reverchon et al, 2002 ; Dietrich et al, 2006 ; Liu and Nizet, 2009 ). Recently, it has been reported that, in non-pathogenic pseudomonads, the synthesis of pigments, peptidases, and biofilm formation increased at low temperature, putatively to overcome the hurdles imposed by cold stress ( Yuan et al, 2018b ; Rossi C. et al, 2018 ; Quintieri et al, 2019a , b ). Some of these biological components also showed a high similarity with those involved in pathogenesis and resistance mechanisms in the opportunistic pathogen P. aeruginosa ( Quintieri et al, 2019b ), although their role in food spoilage pseudomonads is not yet completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing demand of low-salt and low-fat cheese requires new hurdle technologies approaches to reduce the spoilage microbial communities along the shelf life, particularly by psychotropic Gram-negative bacteria [ 33 , 34 ] that can also trigger antimicrobial resistances [ 35 ]. To address this issue, this study focused on the characterization of the spoilage microbiota of these dairy products and the appraisal of lactic acid bacteria adjunct cultures in limiting the outgrowth of these undesirable microorganisms and consequently cheese defects.…”
Section: Discussionmentioning
confidence: 99%
“…Different groups of microorganisms can participate in biofilm formation in dairy processing plants. The attention of biofilm researchers is attracted by Pseudomonas psychrophiles, which secrete heat-resistant lipolytic and proteolytic enzymes, and Geobacillus, Brevibacillus, Paenibacillus, Sporosarcina sporeforming bacteria [7][8][9]. Lactic acid microorganisms are also actively involved in biofilm formation [10,11].…”
Section: Introductionmentioning
confidence: 99%